Functional Ability, Independence, and Comfort in Children with Cerebral Palsy: A Comparative Evaluation of Jointed and Rigid Ankle Foot Orthosis - Hisyam Syafi'ie; Anissa Eka Septiani (Journal of Prosthetics Orthotics and Science Technology, 2026)
Background: Ankle-Foot Orthoses (AFOs) are widely used to improve gait in children with cerebral palsy (CP), yet their effects are multidimensional and vary across functional, independence, and user-centered domains. This study synthesizes clinical outcomes from a diverse CP cohort to inform an integrated, evidence-based approach to AFO prescription. Methods: We conducted a descriptive observational analysis of 40 children with CP using AFOs. Measurements included GMFCS-based functional status, independence with PEDI-2, and comfort/satisfaction with QUEST. Normality was assessed with the Shapiro–Wilk test. Group comparisons between rigid and jointed AFO designs were analyzed with the Mann–Whitney U test; effect sizes were reported as r. Regression analyses identified predictors of independence and comfort. An integrated outcome framework and clinical decision algorithm were developed to guide prescription. Results: The sample (mean age 7.80 ± 4.42 years; mean AFO use 4.56 ± 4.09 years) showed multidimensional effects of AFO design. Rigid AFOs yielded higher GMFCS scores (functional benefit) and a clustering of higher-function outcomes, whereas jointed AFOs achieved greater comfort (QUEST: r ? 0.34) and a broader distribution of satisfaction. Independence (PEDI-2) did not differ significantly by AFO type (p = 0.283; r = 0.17), indicating multifactorial determinants beyond device design. Regression indicated age as a strong predictor of independence, and AFO design as a key predictor of comfort. An integrated framework mapped rigid AFO to function, jointed AFO to comfort/independence, and highlighted the role of wear-time in real-world effectiveness. Conclusion: AFO effectiveness in CP is multidimensional; rigid designs may enhance functional stability while jointed designs improve comfort and potential adherence, influencing participation. An individualized, goal-directed prescription that balances biomechanical control with user-centered outcomes is essential for optimizing short-term performance and long-term participation. Keywords: Ankle-foot orthosis, GMFCS, Comfort, Pediatric rehabilitation, Cerebral palsy